Progress and Prospect of Immunotherapy for Triple-Negative Breast Cancer - Luo, Chenyi; Wang, Peipei; He, Siqi; Zhu, Jingjing; Shi, Yuanyuan; Wang, Jianxun (Frontiers in Oncology, 2022)
Breast cancer is most commonly diagnosed cancer (estimated 2.3 million new cases in 2020) and the leading cause of cancer death (estimated 685,000 deaths in 2020) in women globally (1). Triple negative breast cancer (TNBC), a breast cancer subtype lacking ER, PR and HER2 expression, is associated with high metastatic potential and poor prognosis (3). TNBC accounts for about only 15-20% of new breast cancer diagnoses, it is responsible for most breast cancer-related deaths due to lack of targeted treatment options for this patient population, and currently systemic chemotherapy, radiation and surgical excision remain the major treatment modalities for these patients with TNBC (4). Although breast cancer patients in general do not have robust response to the immunotherapy, a subset of TNBC has been demonstrated to have high tumor mutation burden (TMB) and high tumor infiltrating lymphocytes (TIL), resembling to the features observed on melanoma or lung cancers which can benefit from treatment of immune check point inhibitors (ICI). Therefore, the immunogenic nature of this aggressive disease has presented opportunity for the development of TNBC-targeting immunotherapies (5). The recent FDA approval of atezolizumab in combination with the chemotherapeutic agent nab-paclitaxel for the treatment of PD-L1–positive unresectable, locally advanced, or metastatic TNBC has led to a new era of immunotherapy in TNBC treatment. And immunotherapy becomes an active research area, both in cancer biology field and in oncology field. In this review, we will extend our coverage on recent discoveries in preclinical research and early results in clinical trials from immune molecule-based therapy including cytokines, monoclonal antibodies, antibody-drug-conjugates (ADC), bi-specific or tri-specific antibodies, immune checkpoint inhibitors (ICI) and neoantigen cancer vaccines; oncolytic virus-based therapies and adoptive immune cell transfer-based therapies including TIL, chimeric antigen receptor-T (CAR-T), CAR-NK, CAR-M and T cell receptor-T (TCR-T). In the end, we will list a series of the challenges and opportunities in immunotherapy prospectively and reveal novel technologies such as high throughput single-cell sequencing, CRISPER gene-editing based screening to generate new knowledges of immunotherapy.